Penggunaan Aplikasi Smart Apps Creator untuk Meningkatkan Kemampuan Percakapan di Kelas X - Khatimah, Husnul; Kartini; Arif Pamessangi, Andi; Alahuddin (Pedagogical Education and Review of Linguistics, 2025)
This study aims (1) to determine how the application of Smart Apps Creator application in improving al-hiwar skills in class X MAN Palopo students. (2) To find out how the mastery of al hiwar students before and after the application of Smart Apps Creator application in class X students of Madrasah Aliyah Negeri Palopo. This research procedure was carried out in two cycles, with the Kemmis and Mc taggart model, each cycle going through four stages, namely: planning, implementation, observation, and reflection. Each cycle consisted of two meetings. The data collection methods used were action observation, tests, and field notes. The results of this study are (1) the steps of this study are that the researcher starts the learning by taking students' attendance, then the researcher explains the smart apps creator application and divides students in pairs. After that students memorize the conversation text in the smart epps creator application then the students have a conversation in front of the class. (2) The percentage increase in cycle I can be seen that 26 students, who were complete as many as 17 students with a percentage (65.3%), while those who were not complete were 9 students with a percentage (34.6%). As for the second cycle of 26 students, 24 students were completed with a percentage of (92.3%), while those who had not completed were 2 students with a percentage of (7.7%). From cycle I to cycle II there was an increase in learning outcomes by (27%). Thus in cycle II the learning outcomes were said to be complete.